Application of egg shell with fortified vermicompost in Capsicum cultivation: A strategy in waste management - Ishita Biswas; Debasis Mitra; Debanjan Mitra; Sourav Chattaraj; Ansuman Senapati; Abhinobo Chakraborty; Goutam Basak; Pradeep Das Mohapatra (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Chicken eggshell (ES) is a global biowaste product of poultry industry and an enriched source of calcium required for plant growth. Therefore, the present study has been carried out to assess the potentiality of the combination of ES with vermicompost (VC) and chicken feather protein hydrolysate (CFPH) on growth and yield improvement of Capsicum plants.Method A field study was conducted through randomized block design (RBD) with eight treatments having three replicates for each. Principle Component Analysis (PCA) have performed to analyze the yield related parameters of plant. Nutritional components of VC and ES were also analyzed.Results The PCA analysis of the  field experiment data has indicated that the combination of ES, CFPH and VC (in a ratio of 100:10:3) remarkably increased the agronomic parameters of capsicum plant about four folds as compared to its chemical counterpart and control, while together VC and ES strongly influences the characteristics of fruits. The first two dimensions of first and second PCA analysis showed 88.39 and 66.91 percent of the overall dataset inertia respectively, explaining 88.39 and 66.91 percent of the total variability. These two values are higher than their respective reference values of 36.32 and 46.76 percent indicating substantial variability.Conclusion The co-application of ES, CFPH with VC could enhance the yield parameters of crops by enriching the soil with both micro and macronutrients. It also serves as a source of organic compost with concomitant reduction in the use of chemical fertilizers.